EFFECT OF NEURODEGENERATIVE CHANGES IN THE BRAIN ON THE FORMATION OF THE DISEASE CLINICAL PICTURE IN PATIENTS WITH MULTIPLE SCLEROSIS - L. N. Prakhova; Ye. P. Magonov; A. G. Ilves; A. A. Bogdan; G. V. Kataeva; Ye. S. Malakhova; Zh. I. Savintseva; I. D. Stolyarov; T. N. Trofimova (Бюллетень сибирской медицины, 2013)
The aim of the study was to determine the relationship of global and regional cerebral atrophy and volume of demyelination lesions in the brain with a clinical picture in patients with multiple sclerosis (MS). The study involved 55 patients with MS. Control group included 22 healthy volunteers. Patients were divided into groups according to the severity of disability, the type and duration of disease. Assessment of general and regional atrophy was performed by post-process volumetric segmentation of MRI data, which was acquired at 3T Philips Achieva scanner. The post-processing was done with the FreeSurfer software. It is shown that in MS patients brain atrophy develops both by means of gray matter (including the cortex and subcortical structures), and white matter, along with demyelination. Global and regional atrophy is associated with the severity of disability of patients according to EDSS scale, but not with the duration and type of the disease. Neurodegenerative changes of brain structures evolve with different rates, have different intensity and determine the set of symptoms of neurological impairment and severity of disability, which indicates the presence of certain patterns of the process of atrophy in the brain, forming the clinical picture of the disease.